Issues impacting on enrolled nurse education for Aboriginal and Torres Strait Islander students: a discussion - Cramer, J.; Pugh, J.; Slatyer, Susan; Twigg, D.; Robinson, M. (eContent Management, 2018)
Background: Achieving increased participation of Aboriginal and Torres Strait Islander peoples in Australia’s health workforce, particularly nursing, is federal government policy imperative. However, the uptake of Aboriginal and Torres Strait Islander students into nursing has stalled and their attrition from tertiary nursing courses is considerably higher than for other students. Aim: To alert the profession to issues impacting enrolled nursing education for Aboriginal and Torres Strait Islander students. Design: Discussion paper. Results: Studies of Aboriginal and Torres Strait Islander students mainly focus on tertiary education for registered nurses whereas vocational education and training (VET) for enrolled nurses is usually overlooked. It is generally assumed that the issues influencing the recruitment, attrition, and retention of Aboriginal and Torres Strait Islander students in higher education universities and other institutions similarly impact enrolled nursing students in the VET sector. Conclusion: Research that contributes robust evidence-based knowledge specifically on strategies addressing issues in enrolled nursing education for Aboriginal and Torres Strait Islander students and their employment uptake is required.